Penafsiran Ayat-Ayat Pertanian dalam Al-Qur'an: Studi Komparatif antara Tafsir Al-Mishbah dan Tafsir Ilmi Kemenag RI - Ahmad Rofiud Darojat (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2023)
The utilization of natural resources for food production is vital for meeting the needs and enhancing the welfare of Indonesia. Despite Indonesia's significant agricultural potential, challenges such as land scarcity, fertilizer shortages, pest infestations, and unpredictable global climate changes have impacted the food sector, leading the country to become a rice importer since the 1997 economic crisis. This research aims to examine the interpretation of agricultural verses in the Qur'an by comparing Quraish Shihab's Tafsir Al-Mishbah and the Tafsir Ilmi developed by the Indonesian Ministry of Religious Affairs (Kemenag). Employing a descriptive and comparative literature review methodology, the study utilizes primary sources including the Qur'an, Tafsir Al-Mishbah, and Tafsir Ilmi, alongside secondary sources from various scholarly works. The research addresses two primary questions: (1) What are the similarities and differences in the interpretations of agricultural verses between the two tafsir sources? (2) How do these interpretations contribute to the development of the agricultural sector? Findings indicate that both tafsir emphasize agriculture as an integral part of human life intertwined with spiritual and moral values. Tafsir Ilmi highlights scientific and ecological aspects, while Tafsir Al-Mishbah focuses on philosophical and ethical dimensions. The integration of scientific knowledge and religious values offers a comprehensive framework for sustainable agricultural practices, thereby providing significant contributions to overcoming current agricultural challenges in Indonesia.